Ritual Textualization in the Priestly Traditions of the Hebrew Bible and Late Babylonian Priestly Literature - Debourse, Céline; Rhyder, Julia (Journal of Hebrew Scriptures)

(untitled) (University of Alberta, 2024)
This article explores how the pressures of empire inspired comparable processes of ritual textualization in Persian-period Jerusalem and Late Babylonian temple communities in Uruk and Babylon. We provide the first detailed comparison of the Priestly rituals texts of the Pentateuch and the Late Babylonian temple ritual texts, highlighting several distinctive features they have in common: namely, their concern to integrate their ritual materials into larger corpora that promote priestly hegemony, their interest to articulate ritual behavior in a way that does not rely on royal agency, and their tendency to describe ritual action in an idealized manner. These similarities, we argue, add powerful weight to the theory that the textualization of ritual in the Priestly traditions was inspired by similar historical dynamics to those that informed the textualization of ritual in the Late Babylonian materials; namely, the cultic disruption caused by foreign imperial interference and temple destruction, and the resulting challenges of rebuilding the temple in the absence of a local king with a stake in the cultic restoration.